2021
DOI: 10.3390/ma14206201
|View full text |Cite
|
Sign up to set email alerts
|

Alumina and Zirconia-Reinforced Polyamide PA-12 Composites for Biomedical Additive Manufacturing

Abstract: This work aimed to prepare a composite with a polyamide (PA) matrix and surface-modified ZrO2 or Al2O3 to be used as ceramic fillers (CFs). Those composites contained 30 wt.% ceramic powder to 70 wt.% polymer. Possible applications for this type of composite include bioengineering applications especially in the fields of dental prosthetics and orthopaedics. The ceramic fillers were subjected to chemical surface modification with Piranha Solution and suspension in 10 M sodium hydroxide and Si3N4 to achieve the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 53 publications
3
28
3
Order By: Relevance
“…Combining PA 6 or PA 12 with various additives can increase material properties and enable wider application in the automotive, aerospace, and mechanical engineering industries. Popular additives include aluminum powder [ 39 ]; glass [ 40 , 41 , 42 , 43 ], and carbon fibers [ 44 , 45 , 46 , 47 , 48 , 49 ], as well as self-extinguishing particles (flame retardant) [ 50 , 51 ]; antistatic particles (electrostatic discharge) [ 52 ], and black carbon [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…Combining PA 6 or PA 12 with various additives can increase material properties and enable wider application in the automotive, aerospace, and mechanical engineering industries. Popular additives include aluminum powder [ 39 ]; glass [ 40 , 41 , 42 , 43 ], and carbon fibers [ 44 , 45 , 46 , 47 , 48 , 49 ], as well as self-extinguishing particles (flame retardant) [ 50 , 51 ]; antistatic particles (electrostatic discharge) [ 52 ], and black carbon [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results are part of a broader study on the modification of ceramic filler coatings dedicated to polymer-ceramic composites (PCC) and represent a continuation of our earlier work [40,41]. These fillers have potential applications as an input to PCCs and could be used in 3D printing for dentistry [41,42]. These types of materials may also have significant importance in the case of biomechanical mismatch in metallic alloys that are used for implants.…”
Section: Resultsmentioning
confidence: 56%
“…However, because of its limited osteogenic properties, various studies are related to the increase of the biological activity of PEEK implants [ 34 ]. Nakonieczny et al revealed that zirconia can be used with polymer to prepare composites for biomedical applications such as FDM filament for 3D printing [ 35 ]. Mishra et al found that zirconia particles in PEEK matrix could significantly improve the storage modulus of the nanocomposites [ 36 ].…”
Section: Discussionmentioning
confidence: 99%